2016
DOI: 10.1039/c5tc03152d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of copper nanoparticles within the interlayer space of titania nanosheet transparent films

Abstract: We report the first in situ synthesis of copper nanoparticles (CuNPs) within the interlayer space of inorganic layered semiconductor (titania nanosheets; TNSs) transparent films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Further details of the XRD analyses are summarized in Table S1 (Supporting Information). The initial TNS/MV 2+ film exhibits clear d (002) and (004) signals at 7.8° and 15.3°, respectively, and this is in good agreement with the results of an earlier report . This result indicates that MV 2+ molecules (molecular size: ≈1.3 × 0.4 nm) adopt almost parallel orientations in single layers.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Further details of the XRD analyses are summarized in Table S1 (Supporting Information). The initial TNS/MV 2+ film exhibits clear d (002) and (004) signals at 7.8° and 15.3°, respectively, and this is in good agreement with the results of an earlier report . This result indicates that MV 2+ molecules (molecular size: ≈1.3 × 0.4 nm) adopt almost parallel orientations in single layers.…”
Section: Resultssupporting
confidence: 91%
“…Ogawa and co‐workers and our group have reported the in situ synthesis of various MNPs within the interlayer spaces of layered inorganic compounds. Our technique enables the formation of clear films having strong LSPR extinctions owing to the optical transparency of layered titania nanosheets (TNSs), and relatively large amounts of MNPs are accommodated in their interlayer space.…”
Section: Introductionmentioning
confidence: 99%
“…As already reported in the literature, the exchange of the ammonium ions inside the interlayer of TNSs with metal cations, such as silver, gold, and copper, allows synthesizing in situ plasmonic nanoparticles and nanoclusters . The development of polymeric membranes with embedded metal nanoparticles is of great interest in the nanotechnology field for optical, electrical, and biological applications .…”
Section: Introductionmentioning
confidence: 93%
“…These nanoparticles have been investigated for the fabrication of thin films for optoelectronic applications and in combination with a polymeric matrix for the generation of proton exchange membranes . TNSs were combined with silk fibroin (SF) for the fabrication of nanocomposite thin films and membranes with tunable optical properties and processability at the micro and nanoscale range .…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that methanol was selectively dehydrogenated to methyl formate over Cu/laponite and Cu/ Na(Mg 2.5 Si 4 O 10 F 2 ) clay catalysts, in contrast methanol dehydration to dimethyl ether was the predominant reaction over the Cu/saponite and Cu/montmorillonite catalysts 8 . It was also reported that the interlayer copper ions keep the initial oxidation state even in the reductive reaction conditions 9 . The low activity of copper supported clay catalysts is associated with unavailability of copper for methanol molecules because of its disposition in the interlayer space of the clay 10 .…”
mentioning
confidence: 97%